BIODIVERSITY AND BIOACTIVITY OF STROMATIC XYLARIALES COLLECTED FROM MU KO CHANG NATIONAL PARK, THAILAND - T. SUTJARITVORAKUL; S. CHUTIPAIJIT (My University, 2020)
Ko Chang Island is a tropical rain forest island of Mu Ko Chang national park, Thailand, which has a wide variety of macro-fungi.The objective of this research was to study the biodiversity of Xylariales and to investigate the bioactive activity of ethyl acetate crude extracts.The fungi were collected from the forest area of the waterfalls all over the island.The crude extracts of selected fungi were tested for antibacterial activity by agar well diffusion method and the cancer cell viability was assessed using the MTT assay.Three genera of Xylariaceae and Hypoxylaceae were found including Xylaria, Daldinia and Hypoxylon.The crude extracts inhibited the growth of Gram positive bacteria more than that of Gram negative bacteria and showed broad spectrum inhibition to all cancer cell lines.The crude extract of Xylaria sp.3 showed the highest potential of antibacterial activity and selectively inhibited gastric carcinoma (Kato III) and T cell leukemia (Jurket) with the percentage survival of 26.12 ± 0.90% and 35.37 ± 0.40% respectively.The molecular identification of Xylaria sp.3 was identified as Xylaria sp.TP5BS101.These results show that these macromycetes are an excellent repertoire of antibacterial activity and exhibit anticancer activity against Kato III and Jurket by inducing DNA fragmentation.
Keywords: Geological Studies and Exploration